Ibn-seena - Niazi javed abu (paramount,Paramount Books (Pvt.) Ltd Pakistan, 2016)
"Ibn Sina, or Avicenna, was a Persian polymath celebrated for his groundbreaking works in medicine, philosophy, and science, including The Canon of Medicine."